Influence of co-current vapor flow on falling film over horizontal tube - Furqan Tahir (14429547) (2021)
In the multi-effect evaporator (MED), the seawater falls on the outside of the tube, and the heat is transmitted from the steam flowing inside the tube. As a result, part of seawater evaporates and vapor is generated. Vapor flows in either co-current direction, cross direction or combination of both. The vapor flow exerts external force on falling film and affects film hydrodynamics, heat and mass transfer. This study focuses on analyzing the effects of co-current vapor flow on falling film distribution and hydrodynamics. A two-dimensional (2D) computational fluid dynamics model is developed and validated, in which sea water enters at 65 °C, which represents the maximum limit of current MED plant, and falls on a tube of 25.4 mm diameter from a 2 mm orifice. First, the liquid load is varied between 0.02 and 0.05 kg/(m·s), and its effects on the film thickness and the wetting time are calculated, presented and discussed. Afterwards, the impact of co-current vapor flow on film distribution, wetting time, minimum thickness and its location are quantified and examined by increasing the vapor velocity up to 6 m/s with 2 m/s intervals. It is found that the vapor flow significantly affects the film distribution on the upper half of the tube. The average film thickness and wetting time is reduced by 14.1% and 18.5%, respectively for the vapor velocity of 6 m/s compared to the no vapor flow, for 0.02 kg/(m·s). In addition, the minimum film thickness decreases by 23.1% for 0.02 kg/(m·s). The high decrement in film thickness can lead to dry patches and scale deposition in case of evaporation. Other Information Published in: International Journal of Thermal Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijthermalsci.2020.106614